90 – year glorious history of Vietnam Communist Party - Lê Tố Anh (Tạp chí Nghiên cứu Khoa học Công đoàn, 2021)
The birth of the Communist Party of Vietnam marked a great milestone in Vietnam’s revolutionary history, prepared for the succession of Vietnam Revolution. Since its inception, the Party has successfully led the struggle for power in 1930 - 1945, the resistance against the French colonialists in 1945 – 1954, the resistance against the American imperialism in 1954 – 1975, the comprehensive renovation of the country from 1986 to present. The 90 – year glorious history of the Party is plentiful and diverse with the mighty history pages, give us lots of emotions. The author provides some receipts, initial evaluation subjectively. We all recognize and respect the Party's contributions to the nation and era, join hands in building the strong Party , make the Party to always be the pillar of the revolution, continue to leading Vietnam to its aim, is to create " Rich people – strong nation – equitable, democratic and civilized society”